2020
DOI: 10.1186/s12912-020-00439-5
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ intention to leave their job and associated factors in Bahir Dar, Amhara Region, Ethiopia, 2017

Abstract: Background Intention to leave is an employee’s plan of tendency to leave the current working institute to find an alternative job in the near future. Even though nurses are the backbone of patient caring, there was no study done on intention to leave their job in North West Ethiopia. Therefore, the aim of this study was to assess nurses’ intention to leave their job and associated factors in Bahir Dar, North West Ethiopia, 2017. Methods An institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 46 publications
4
31
0
Order By: Relevance
“…The purposes of the 32 pre-COVID-19 articles can be viewed in Table 3 . The purposes included assessing nurses’ turnover intention rates [ 24 , 29 , 38 ], identifying nurses’ turnover intention factors [ 10 , 14 , 44 ], and examining the association of turnover intention with variables such as job satisfaction, leadership style, burnout, and work climate [ 11 , 23 , 39 , 40 ]. In summary, we can conclude that most post-COVID-19 studies aimed to examine the psychological impacts of the pandemic on nurses’ turnover and turnover intention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purposes of the 32 pre-COVID-19 articles can be viewed in Table 3 . The purposes included assessing nurses’ turnover intention rates [ 24 , 29 , 38 ], identifying nurses’ turnover intention factors [ 10 , 14 , 44 ], and examining the association of turnover intention with variables such as job satisfaction, leadership style, burnout, and work climate [ 11 , 23 , 39 , 40 ]. In summary, we can conclude that most post-COVID-19 studies aimed to examine the psychological impacts of the pandemic on nurses’ turnover and turnover intention.…”
Section: Resultsmentioning
confidence: 99%
“…In the reviewed articles, job-related characteristics such as clinical assignment, job demand, passiveness, and workload significantly predicted nurses’ turnover intention [ 4 , 11 , 30 ]. In addition, while recognition was associated with lower nurses’ turnover intention [ 3 , 24 , 33 ], workplace bullying was associated with higher nurses’ turnover intention [ 7 , 28 ]. Vévoda, Vévodová, Bubeníková, Kisvetrová, and Ivanová; and Wubetie et al found that salary is associated with nurses’ turnover intention [ 2 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A self-reported administered questioner was used in the current study. However, an ergonomic measurement tool was used in the former study [ 26 , 27 ]. As a result, the findings from the self-reported questioner could be overestimated or underestimated compared with ergonomic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Better understanding of the factors that affect recruitment and retention of nurses to work in the oncology specialty is important and could help to inform future strategy in line with the 'Saudi Vision 2030' [16]. The current study aims to explore these issues in greater depth by examining what influences nurses' intention to work in the oncology specialty, where intention is defined as a mental process of planning to either work, stay, or leave the oncology specialty [17]. Specifically, to inform the development of a Saudi oncology nursing workforce that can deliver effective palliative care, this study aimed to address two research questions: 1) What are the intentions of three different groups of nurses in Saudi Arabia toward working in the oncology specialty, and 2) what factors influence nurses' intention toward working in oncology nursing.…”
mentioning
confidence: 99%